Postoperative handover: problems, pitfalls, and prevention of error. - Nagpal, K; Arora, S; Abboudi, M; Vats, A; Wong, H; Manchanda, C; Vincent, C; Moorthy, K (2010)
OBJECTIVE: To identify the information transfer and communication problems in postoperative handover and to develop and validate a novel protocol for standardizing this communication. BACKGROUND: Effective clinical handover ensures continuity of patient care. Patient handovers within surgical units are largely informal. A thorough understanding of the problem is vital to develop standardized protocols. METHODS: A qualitative semistructured interview study was conducted with 18 healthcare professionals to uncover the problems with postoperative handover and to identify solutions, including components of a postoperative handover protocol. Interviews were recorded, transcribed verbatim, and submitted to emergent theme analysis. Multiple blind coders were used to ensure triangulation and reliability of the coding process. A Delphi method was used to elicit consensus from a group of 50 surgical professionals so as to validate the handover protocol. RESULTS: Many of the information transfer and communication failures at the postoperative phase are deemed to be due to an incomplete handover. All the interviewed healthcare professionals agreed that postoperative handover should be structured in the form of a standardized protocol so as to prevent omissions of any critical information. Based on this, 28 items were submitted to the Delphi process. Of these, 21 items had a mean importance score greater than 4.0 and were included in the final postoperative handover proforma under the following headings: patient-specific information, surgical information, and anesthetic information. CONCLUSION: The present study identified that the postoperative handover is informal, unstructured and inconsistent with often incomplete information transfer. Based on end-user input, a handover protocol was successfully developed and validated. Use of this may facilitate standardization of this critical activity and thereby improve the quality of patient care.